Amphetamine Type Stimulants Use Among Methadone Clients In Klang Valley - Wan Ahmad Kamal, Wan Maisarah (2020)
This study aimed to understand the context of ATS use, perceptions towards ATS use and the availability of psychosocial components in MMT program. A total of 231 respondents were recruited through convenience sampling from two MMT facilities (primary vs. private) in Klang Valley for this cross-sectional study.